PEMBENTUKAN IDENTITAS DIRI ANGGOTA KOMUNITAS EXO - L BANDUNG - Kumala Hayati; Mohamad Syahriar Sugandi (Dialektika, 2017)
K-POP or Korean Pop is term for Korean Fever or Korean Wave which focused in fashion, film, drama, and music, has become trendsetter which followed by youngster and bring K-POP artists, called Hallyu Star to Indonesia. One of them is EXO, who has begun their debut on April 2012 with mini album, MAMA. The popularity of EXO, seen from the established of fans community in Bandung, called EXO – L Bandung which every activity to support EXO. Every member who join community, without realized, it will form self identity as fans of EXO which seen from daily activity of them. It will bring up self concept which show how theirself want to look as fans of EXO. This study disscuss about how self identity formation in community member, how they meaning their identity as fans of EXO which show at daily activity, until it bring them to self concept which how they want seen as fans of EXO by others. This study use qualititative method with fenomenology approachment and non structure interview technique and observation and literature study. According to the result of research and disscusion, is known that the process of identity formation community members affected by the public (society) where people nearby such as family and friends (significant other), then, bias (favorite member of EXO) and the community itself (generalized other), the meaning of fans from the mind, is shown through the selection of lifestyle which their do, then raises their self-concept (self) as a loyal fan, and adults, the changes of taste to Korea, the desire to be a figure of EXO or have a partner like EXO and go to Korea to meet with them.